Kepuasan Kerja Guru (Studi Korelasi Antara Iklim Organisasi dan kepemimpinan Kepala Sekolah Dengan Kepuasan Kerja Guru) - Isman Kada (Universitas Pakuan, 2013)
This study aims to determine the relationship between organizational climate and job satisfaction of teachers and school leadership to teacher job satisfaction and jointly between organizational climate and leadership skolah with teacher job satisfaction. Research conducted at the Junior High School located in the eastern district of Bogor by civil service teachers as many as 154 samples randomly selected people (proportional random sampling). The method of collecting research data in the field using survey methods, while the statistical analysis using the technique of correlation analysis, simple regression analysis, and multiple regression analysis. Measurements taken hypothesis at significance level ? = 0:05 and at significance level ? = 0.01, respectively.Based on the calculation results obtained from the three main research results are: First, there is a positive relationship and very significant between organizational climate and teacher job satisfaction indicated by a correlation coefficient of 0.38 and a coefficient ry1 r2y1 determinant of 0.3906, thereby contributing Organizational Climate variables (X1) to the professional competence of teachers (Y) of 39.06%. This means that the variation of teacher job satisfaction is determined by the Organizational Climate. Secondly, there is a positive relationship and very significant between school leadership and job satisfaction of teachers indicated by a correlation coefficient of 0.4395 and ry2 r2y2 determinant coefficient of 0.1928, so the contribution of variable X2 to Y by 19.28%. This means that the variation of teacher job satisfaction is determined by the Principal Leadership. Third, there is a very significant positive relationship between motivation and work and school leadership together with job satisfaction of teachers demonstrated by multiple correlation coefficient (ry2.12) amounted to 0,467, and the determinant coefficient so that the contribution of X1 and X2 to Y by 46 , 70%. This means the variation that occurs in teacher job satisfaction is determined jointly by the Climate Organization and the leadership of the Principal.Keywords : Climate Organization, Work Motivation, Principal Leadership